Komunikasi Moderasi Pesantren; Studi Kasus Kepemimpinan Pesantren Nurul Huda Paowan Situbondo - Abdul Hadi (FALASIFA : Jurnal Studi Keislaman, 2020)
The pesantren moderation life is a cultural agent of noble religious life. As understood together, that Kyai is a source of pesantren culture. The success of the institution's moderation culture, is certainly inseparable from the communication patterns in creating an important component in the pesantren moderation culture. Based on that opinion, this research is very important to do. This study examines the pesantren leadership model in developing its moderation culture. The study will be conducted using a qualitative phenomonological approach. After conducting in-depth study, the discussions can be concluded that leadership communication is carried out based on the kyai knowledge and awareness. In the process, there are several important things to be found, namely, first, purposes. It includes informing, influencing or persuading, instructing and engaging moderation process. Second, the compilation of messages based on weakness of pesantren moderation and feedback shown by the pesantren society. Third, the selection of communication channels which includes verbal (meeting communication and the important meeting others) and nonverbal (uswah action and postering).